A novel continuous control set model predictive control to guarantee stability and robustness for buck power converter in DC microgrids. (November 2021) - Zhou, Jiyao; Hassan, Mustafa Alrayah; Zhang, Jiaxuan; Zhang, Zehua; Wu, Shang; Hou, Mingxuan; Li, Yongjian; Li, Erping; Guerrero, Josep M.
Abstract: In this paper, an adaptive continuous control set model predictive control (CCS-MPC) is proposed to eliminate the instability problem caused by the constant power load (CPL) in DC–DC​ buck converter applied in DC microgrids. Based on the dynamic model of energy storage elements(inductor and capacitor) in circuit, a parallel feedforward algorithm (PFA) is designed to estimate the variation of the load and input voltage. By supplying the information of the variation to the CCS-MPC controller, the large signal stability and fast recovery performance can be ensured under the existence of disturbances. To verify the control robustness of the adaptive CCS-MPC controller, the MATLAB simulations, hardware-in-loop (HIL) experiments and rapid-control-prototype (RCP) experimental results are conducted. Moreover, the comparative simulations and HIL experiments towards other nonlinear controller are conducted to investigates its dynamic performance.